La literatura tartésica. Fuentes históricas e iconográficas - Almagro-gorbea, Martín (Gerión. Revista de Historia Antigua, 2005)
Strabo (III,3,6) speaks about the existence of literature in Tartessos. These topic has been forgotten in recent studies. These analysis is based on the fact that oral and written literature and iconography are interrelated languages, which allow identify several mythical and historical texts known through classical authors and iconography, as the relieves from Pozo Moro and orientalizing bronzes and ivories; There also were sacred poems and legal texts. Tartessian literature began in Late Bronze Age and can be compared to other literatures of the Mediterranean cultures in Antiquity. However, Tartessian mythology was so influenced by Phoenician mythology as Etruscan and Roman ones by the Greek mythology. These Tartessian literature is basic to understand the Phoenician colonization in Western Mediterranean, the Tartessian culture and the process of assimilation and cultural change in the Mediterranean through Antiquity.